RESEARCH ON THE REFORMS CARRIED OUT TO RESTORE THE SCIENTIFIC AND EDUCATIONAL HERITAGE OF SUFI SCHOLARS IN THE INDEPENDENCE YEARS UZBEKISTAN - Khatamov Tokhir Abdumutalovich (Bright Mind Publishing, 2025)
This article explores the process of studying and restoring the centuries-old scientific and educational heritage of Sufi schools in Central Asia during the reforms carried out in Uzbekistan. The primary reason for focusing on the reforms of the independence years is that the Republic of Uzbekistan achieved independence after breaking free from colonial chains in the second half of the 20th century. As history shows, states that achieve independence tend to pay primary attention to restoring their history, religion, language, and culture. In the process of the systematic and gradual restoration of our national values, the national-legal foundation plays an important role. In this regard, the decrees and decisions issued by the President and government in the early years of independence, along with their scientific-historical and socio-cultural significance, have been analyzed. The priority tasks outlined in the decrees and decisions, as well as the importance of the work that needs to be done according to plans and programs, have been highlighted.
Keywords: Reforms, decrees, decisions, Islam, Sufism, scholars, Naqshbandiya, tariqat, sheikh, mysticism, scientific school, scientific research.